Das Geheimnis der Wiederholung: Sören Kierkegaard passiert jüdisches Denken - Blättel, Richard (transcript, 2016)
Kierkegaard's filtering of Jewish thought. In analysing this process, a spiritual affinity develops that sheds new light on his philosophy.